Investigating Teachers’ Perceptions of the CEFR-Aligned Curriculum in Primary Education: Bridging Policy and Practice (Contrarius Series: Law & Social Justice, 2026)
The Common European Framework of Reference (CEFR) has gained widespread international recognition as a global framework for language education, extending far beyond its original European context. As part of this global trend, Malaysia has implemented a CEFR-aligned English language curriculum, requiring teachers to adapt their pedagogical practices to internationally benchmarked standards. The success of such large-scale curriculum reforms depends heavily on teachers’ knowledge, acceptance, and interpretations of the framework. While previous studies have examined CEFR implementation across various contexts, empirical research integrating teachers’ knowledge and perceptions through mixed-methods approaches remains limited, particularly in non-European settings. Employing an explanatory sequential mixed-methods design, this study investigates Malaysian primary school English teachers’ understanding of key CEFR components and their perceptions of their influence on classroom practice. Data were collected through questionnaires and semi-structured interviews, with quantitative data analyzed using descriptive statistics and qualitative data examined through thematic analysis. The findings reveal a notable discrepancy between teachers’ generally positive perceptions of the CEFR-aligned curriculum and their insufficient understanding of core CEFR concepts, including proficiency levels, descriptors, and underlying principles, despite having received formal training. This gap poses significant challenges for meaningful classroom implementation. By highlighting disconnect between policy intentions and teachers’ CEFR literacy, this study contributes to international discussions on CEFR adoption, teacher cognition, and curriculum reform. The findings underscore the need for sustained, conceptually oriented professional development and offer transferable insights for policymakers and educators in other contexts adopting CEFR-based frameworks.